2007
DOI: 10.1016/j.ijgo.2007.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Association of intimate partner physical and sexual violence with unintended pregnancy among pregnant women in Peru

Abstract: The findings indicate the need to include IPV screening and treatment in prenatal care and reproductive health settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
85
1
7

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(109 citation statements)
references
References 16 publications
16
85
1
7
Order By: Relevance
“…Another important new finding was that a combination of both physical and sexual IPV appeared to have more profound consequences on the outcome measured. Previous studies found that experienced of both physical and sexual IPV are stronger predictors of long-term negative physical and mental health outcomes of mothers (Ferri et al, 2007;Peter, 2004;Cripe et al, 2008;Bizu et al, 2010). Its impact on mental health can be as serious as its physical impact, and may be equally long lasting.…”
Section: Discussionmentioning
confidence: 96%
“…Another important new finding was that a combination of both physical and sexual IPV appeared to have more profound consequences on the outcome measured. Previous studies found that experienced of both physical and sexual IPV are stronger predictors of long-term negative physical and mental health outcomes of mothers (Ferri et al, 2007;Peter, 2004;Cripe et al, 2008;Bizu et al, 2010). Its impact on mental health can be as serious as its physical impact, and may be equally long lasting.…”
Section: Discussionmentioning
confidence: 96%
“…U odnosu na žene sa željenom trudnoćom one su pod 2,5 puta većim rizikom od fizičkog zlostavljanja tokom trudnoće [12].…”
Section: Wwwtmgorgrsunclassified
“…Existe evidencia de las graves consecuencias, directas e indirectas, que ocasiona la violencia de pareja en la salud de la mujer (2)(3)(4)(5) . La prevalencia de violencia física o sexual contra la mujer por la pareja es alta aunque puede variar según los ámbitos geográficos.…”
Section: Introductionunclassified
“…Prevalence of physical violence at the national level was 14,5%, with variations according to the geographical areas (9,7% to 18,9%). The factor associated to a higher risk is having a couple who frequently gets drunk (OR: 7,2; 95%CI: 5,4-9,6) and having a couple controlling or limiting the woman's visits to family or friends (OR: 4,1; 95%CI: 3,(3)(4)(5)0); other associated factors are history of physical aggression of the father to the mother, having had previous partners, be cohabiting, having a higher educational level than the partner and having a disbalanced decision taking in the couple. Among the factors associated with a lower risk are the communication and respect inside the couple (OR: 0,3; 95%CI: 0,2-0,3), and the fact that the woman has health insurance.…”
mentioning
confidence: 99%